PENGGUNAAN MEDIA KARTU HURUF UNTUK MENINGKATKAN LITERASI PADA SISWA KELAS II DI SDK NUABOSI - Yosefa Kafasin Owa; Pelipus Wungo Kaka (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
Beginning reading is the initial process in learning to read activities that are trained with letters and syllables in low grade students. However, many students who are in grade II SD have difficulty in learning beginning reading, because the researcher's efforts in improving beginning reading, one of which is to apply the use of letter card media to encourage student enthusiasm and interest, the research subjects to be studied are all students of SDK Nuabosi in grade 2, totalling 16 students, consisting of 10 male students and 6 female students. This research design uses the Classroom Action Research (PTK) model, there are several cycles in this study, each of which has 4 components, namely planning, implementation, observation and reflection. The results of the practice of learning activities in cycle II with games using letter cards received a score of 87% with a percentage increase of 76.9%, so the percentage of success of the data obtained has exceeded the expected success criteria of 70%.